Multidisciplinary Care: Facial Reanimation in the Pediatric Population - Mohan, Vamsi C.; Akram, Muhammad; Belfort, Benjamin D.; Abu-Ghname, Amjed; Xue, Amy S. (Seminars in Plastic Surgery, 2025)
Facial reanimation refers to the array of options available to manage patients with facial nerve injury or palsy. From congenital to acquired etiologies, a multidisciplinary approach and team is needed to treat the functional and aesthetic deficits these patients may experience. This is particularly true in the pediatric population, who frequently experience significant psychosocial stress from their peers, and cannot adequately voice their experiences due to age. The purpose of this article is to highlight the multidisciplinary team members, their roles, and provide our perspective at Texas Children's Hospital.
Keywords: facial nerve; multidisciplinary team; facial reanimation; plastic surgery; reconstruction